A Randomized Controlled Study to Evaluate the Impact of Instrument and Laparoscope Length on Performance and Learning Curve in Single-Incision Laparoscopic Surgery. (December 2015) - Balaji, Sathyan; Singh, Pritam; Sodergren, Mikael H.; Corker, Harry P.; Kwasnicki, Richard M.; Darzi, Ara; Paraskeva, Paraskevas
Introduction . The proximity of instrumentation in single-incision laparoscopic surgery (SILS) creates ergonomic challenges. An innovative method to reduce external collisions between instruments and handles is to use instruments of different lengths. This study evaluated the impact of instrument and laparoscope length on simulated SILS performance. Methods . Performance was assessed using peg transfer (PEG) and pattern cutting (CUT) tasks from the Fundamentals of Laparoscopic Surgery (FLS) curriculum. Following baseline testing, surgeons were randomized into 3 trial arms: Control—standard length instruments and standard length laparoscope; group 1—one long instrument, one standard length instrument and standard length laparoscope; and group 2—standard length instruments and long laparoscope. Two phases were undertaken using a validated SILS-modified FLS box trainer: phase 1—25 repetitions of PEG and phase 2—5 repetitions of CUT. FLS scoring parameters measured performance and the Imperial College Surgical Assessment Device (ICSAD) captured motion analysis of hands. Results . Twenty-three surgeons were recruited—control (n = 7), group 1 (n = 9), and group 2 (n = 7). No significant differences were observed in operative experience or baseline skills performance. Phase 1: Peak FLS score was significantly higher in group 1 compared with control ( P = .009). Comparison of learning curves revealed learning plateau was significantly higher in group 1 compared with control ( P = .010). Phase 2: Group 1 revealed a trend toward higher peak FLS scores over the control ( P = .067). No significant differences in motion analysis of hands were demonstrated using ICSAD. Conclusions . This study demonstrates that using instruments of different lengths can improve simulated SILS performance.